Cultural Robotics: The Culture of Robotics and Robotics in Culture. (5th December 2013) - Samani, Hooman; Saadatian, Elham; Pang, Natalie; Polydorou, Doros; Fernando, Owen Noel Newton; Nakatsu, Ryohei; Koh, Jeffrey Tzu Kwan Valino
In this paper, we have investigated the concept of "Cultural Robotics" with regard to the evolution of social into cultural robots in the 21st Century. By defining the concept of culture, the potential development of a culture between humans and robots is explored. Based on the cultural values of the robotics developers, and the learning ability of current robots, cultural attributes in this regard are in the process of being formed, which would define the new concept of cultural robotics. According to the importance of the embodiment of robots in the sense of presence, the influence of robots in communication culture is anticipated. The sustainability of robotics culture based on diversity for cultural communities for various acceptance modalities is explored in order to anticipate the creation of different attributes of culture between robots and humans in the future.